1-Butylpyridinium bis(1,2-dicyanoethene-1,2-dithiolato)nickelate(III) - Duan, Hai-Bao (International Union of Crystallography, 2011)
The Ni(III) atom in the anion of the title complex, (C(9)H(14)N)[Ni(C(4)N(2)S(2))(2)], is coordinated by four S atoms of two maleonitriledithiolate ligands, and exhibits a square-planar coordination geometry.